Prevalence of orofacial pain in adults with cleft lip/palate - Ravazzi, Gloria (2021)
Objective: Functional disorders in individuals with cleft lip and palate (CL/P) can compromise structures of the stomatognathic system, which is one of the causes of orofacial pain in this group of patients. Numerous mechanisms of orofacial pain, particularly painful temporomandibular disorders (TMD-P), may be related to these conditions and have the potential to be the cause of diffuse. So, the objective of research wasdetermine the prevalence of orofacial pain using validated instruments on individuals with CL/P. Materials and Methods: a observational study was conducted with an intentional random sample of patients with CL/P (n = 80). Two questionnaires were administered: a screening scale for painful TMD (AAOP) and the Graded Chronic Pain Scale (GCPS). Results: In the AAOP screening questionnaire, 75% of individuals with CL / P answered affirmatively to at least one question. The most significant questions were those related to noise (p = 0.007), mandibular movement (p = 0.032) and orofacial pain region (p = 0.044) demonstrated the importance of investigating TMD-P. Regarding the impact of chronic pain in relation to activities of daily living (GCPS), although no significant, it showed that for most individuals with CL / P, it has a low disability, regardless of its intensity (low / high), being more prevalent in older individuals (p = 0.013). Conclusions: the investigation of orofacial pain should be part of the routine at services that work with CL/P patients and should be counseled to seek help for such pain, which can affect their daily living.